Recovery of Silver from Waste X-Ray Film by Alkaline Protease from Conidiobolus coronatus - Shankar, S; More, SV; Laxman, R Seeta (Kathmandu University Journal of Science, Engineering and Technology, 2010)
The waste X-ray/ photographic films contain 1.5 - 2 % (w/w) black metallic silver which is recovered and reused. Around 18-20% of the world's silver needs are supplied by recycling photographic waste. Since silver is linked to gelatin in the emulsion layer, it is possible to break the same and release the silver using proteolytic enzymes. Alkaline protease from Conidiobolus coronatus was investigated for enzymatic hydrolysis of gelatin from waste X-ray films. At the end of the treatment, gelatin layer was completely removed leaving the polyester film clean and silver was recovered in the hydrolysate, both of which can be reused. Various parameters such as pH, temperature, enzyme concentration, time etc on silver removal from the film were studied. Gelatin hydrolysis was monitored by measuring increase in turbidity in the hydrolysate, which was accompanied by release of protein and hydroxyproline. Gelatin layer was stripped completely within 6 min with 1.35 U ml-1 of protease at 40°C, pH 10. Rate of gelatin hydrolysis increased with increased in protease concentration. The enzyme could be effectively reused for four cycles of gelatin hydrolysis. Silver in hydolysate was around 3.87% (w/w) based on total weight of sludge. Key words: Silver recovery; X-ray films; gelatin hydrolysis; alkaline protease; Conidiobolus coronatus DOI: 10.3126/kuset.v6i1.3311 Kathmandu University Journal of Science, Engineering and Technology Vol.6(1) 2010, pp60-69